2010
DOI: 10.1113/jphysiol.2010.188979
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and postsynaptic modulation of monosynaptic reflex by GABAA receptors on turtle spinal cord

Abstract: There is growing evidence that activation of high affinity extrasynaptic GABA A receptors in the brain, cerebellum and spinal cord substantia gelatinosa results in a tonic inhibition controlling postsynaptic excitability. The aim of the present study was to determine if GABA A receptors mediating tonic inhibition participate in the modulation of monosynaptic reflex (MSR) in the vertebrate spinal cord. Using an in vitro turtle lumbar spinal cord preparation, we show that conditioning stimulation of a dorsal roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…; Salin & Prince, ; Bautista et al . ), yet the impact varies across brain region and cell type (Lee & Maguire, ). Moreover, tonic activation does not necessarily imply tonic inhibition and spike suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Salin & Prince, ; Bautista et al . ), yet the impact varies across brain region and cell type (Lee & Maguire, ). Moreover, tonic activation does not necessarily imply tonic inhibition and spike suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Tonic activation of extrasynaptic GABA A Rs regulates neuronal excitability (Otis et al 1991;Salin & Prince, 1996;Bautista et al 2010), yet the impact varies across brain region and cell type (Lee & Maguire, 2014). Moreover, tonic activation does not necessarily imply tonic inhibition and spike suppression.…”
Section: Sources Of Gaba In Mouse Lsomentioning
confidence: 99%
“…Previously, we reported that the monosynaptic reflex evoked by electrical stimulation of one dorsal root in the adult turtle spinal cord was facilitated by furosemide without affecting the dorsal root potential [15] . Knowing that furosemide increases the excitability of cerebellar granule cells by blocking extrasynaptic α 6 subunit-containing GABA A receptors [8] , [9] , [20] , [21] , we decided to test whether the facilitation of the monosynaptic reflex was mediated by a similar mechanism in motoneurons.…”
Section: Resultsmentioning
confidence: 92%
“…Previously we showed that motoneuron excitability might be modulated by high affinity GABA A receptors mediating a tonic inhibitory current [14] , [16] , and that the monosynaptic reflex is facilitated by furosemide without affecting the dorsal root potential [15] . Taken together, these results suggested the presence of furosemide-sensitive GABA A receptors in motoneurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation